Transformasi produk alat masak nasi pada masyarakat Sunda sebagai basis segmentasi pasar - Ghia Tri Jayanti; Meita Annisa Nurhutami (Institut Seni Indonesia Yogyakarta, 2022)
Cooking is a routine in the household to fulfill basic human needs. This study examines the development and changes in cooking activities in Sundanese society, characterized using tools, the cooking process, the efficiency of cooking procedures, and the values adopted in cooking activities. The approach used in this study is an ethnographic design approach and participatory observation. The purpose of this study is to observe changes in rice cooking activities and their transformation in terms of cooking utensils design, cooking process, and cooking habits, as well as their effect on changes in rice cooking design and activities with a case study of traditional houses in Sundanese people. The habits and development of traditional rice cooking utensils and traditional cooking habits and their significant changes in semi-modern and modern products in traditional Sundanese houses in Kampung Naga, Tasikmalaya, West Java were observed in a participatory manner. The findings of changes and developments in culture, habits, processes, and designs on rice cookware products are used as a basis for market segmentation for rice cookware products which are divided into two main market segments which can later be used for the needs of the target users to design products with cultural values, product efficiency, and the value of the product to the user. The two main segments are the home and business segments, which are divided into more specific segments. Specific segments for the home segment are ordinary and extraordinary households. In contrast, the business segment is divided into accommodation providers, food and drink service providers, and other service sectors.